Designing for Metaphor in a Study of Adult Educators: An Exploration and Critique of Metaphor Analysis - Abigail W. Konopasky; Earle Reybold (Adult Education Research Conference, 2014)
The authors argue that designing for metaphors in case study can offer insight into how adult educators view their roles and responsibilities in the classroom. They also critique metaphor analysis, arguing that, like all dialogue with participants, metaphors must also be analyzed within the space of the interview.